Studies on Distribution of Organic Phosphorus in Humus Fractions of Some Soils of Rajasthan - Somani, L L; Saxena, S N (Annals of Arid Zone, 2016)
Regular decreases in the organic phosphorus content with depth are recorded in nine soil profiles of Rajasthan. The organic phosphorus present in various humus fractions (expressed as ppm in oven dry soils) also changes in the analogous pattern. Of the total organic phosphorus present in these soils 35.2 to 74.8 per cent was found to be associated with humus fractions. The Humic acid P/Fulvic acid P ratio varied from 0.43 to 5.78. Variations in constitutional components of phosphorus present in various humus fractions were observed.